PENGARUH PROFITABILITAS DAN GOOD CORPORATE GOVERNANCE TERHADAP PRICE TO BOOK VALUE PADA BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011 – 2013 (Students' Journal of Accounting and Banking, 2015)
The purpose of this research is to examine the influence of Return on Assets, Return on Equity, Return on Investment, and Good Corporate Governance through Price to Book Value of public banking listed at Indonesian Stock Exchange during 2011-2013. Population of this research are Commercial Bank that registered in Indonesian Stock Exchange from 2011 till 2013. Data on this research are coming from Indonesian Stock Exchange (BEI) and Financial Services Authority of Indonesia (OJK). Samples are choosen by purposive sampling method at least 27 company. Data’s test technique by using multiple linear regression analyze. The result showed that Return on Assets, Return on Equity, and Good Corporate Governance have a negative effect but not significant on Price to Book Value. While Return on Investment has a positive effect but not significant on Price to Book Value.Keywords: Return on Assets, Return on Equity, Return on Investment, Good Corporate Governance, and Price to Book Value